BBA home financing setting in Malaysia - Mohd Zulkifli Muhammad; Minah Japang; Zakiah Hassan (Universiti Malaysia Sabah, Malaysia, 2011)
In Malaysia, the issues of home purchasing processes is seen as a complicated and subjective issues as the rapid urbanization in Malaysia seems have strived developer competing with each other to attract public interest in home financing despite providing alternative attractive packages in order to increase their sales. During the 1997 Asian Financial Crisis, home financing activities seems to be deliberately slow as the result of higher interest rates, depressed housing prices, rising unemployment and declining incomes. In addition the quality of property loan was more affected than individual mortgage loan, which proved elastic to external shocks even when credit underwriting conditions were stretched. The fundamental purpose of this paper is to examine two approaches of home financing option namely conventional housing payment and Bai Bithaman Ajil (BBA) financing in the context of housing market. BBA home financing is an Islamic housing payment facility, which is based on the Syariah concept of Bai Bithaman Ajil or in short BBA. It is a unique contract of deferred payment sale on Islamic home financing. Here, we look into the concurrent conventional home financing activities offered by the conventional banking system and Islamic home financing offered by Islamic banks. The study carried out descriptive statistics in comparing the two home financing options as well as look through the involvement of government support housing finance agencies.